MARRIAGE HISTORY FROM THE ERA OF POLYGAMY TO MONOGAMY: THE PERSPECTIVE OF QS ANNISA VERSE 3 - Muhammad Juni Beddu (Marwah: Jurnal Perempuan, Agama dan Jender, 2023)
ABSTRACT:The purpose of this research is to explore the history of marriage in Islam, especially the changes in marriage practices from the era of polygamy to monogamy, with an emphasis on the message contained in QS Annisa Verse 3. This research also aims to understand the impact of this message on modern Islamic marriage practices. This research method involves historical analysis and literature review. Data was collected through the study of Al-Quran texts, commentaries, Islamic history books, and related research. This study also explores the views of scholars on this theme. The results of the study reveal that the practice of marriage in Islam has undergone significant changes over time. From the early days of Islam which involved profuse polygamy, slowly, Muslim societies began to adopt the practice of monogamy as the norm. Verse 3 in QS Annisa provides ethical guidelines regarding polygamous marriages, emphasizing the importance of fairness in the marriage relationship. This influences the understanding and practice of marriage in modern Islam. This research results in a deeper understanding of the history of marriage in Islam and how the messages in QS Annisa Verse 3 have influenced changes in marriage practices. The main impact is that the message about justice and the protection of women's rights in marriage remains relevant in the context of modern Islamic marriage. The conclusion of this study is that the history of marriage in Islam reflects the evolution from polygamy to monogamy, with an emphasis on justice and protection of women's rights in marriage. The message in QS Annisa Verse 3 continues to guide the practice of marriage in Islam today, emphasizing the importance of ethics and equality in marriage relations.Keywords: History, Marriage, Polygamy, Monogamy, Perspective QS Annisa Verse 3ABSTRAK:Tujuan penelitian ini bertujuan untuk menggali sejarah pernikahan dalam Islam, terutama perubahan praktik pernikahan dari era poligami menuju monogami, dengan penekanan pada pesan yang terkandung dalam QS Annisa Ayat 3. Penelitian ini juga bertujuan untuk memahami dampak pesan ini pada praktik pernikahan Islam modern. Metode penelitian ini melibatkan analisis historis dan kajian literatur. Data dikumpulkan melalui studi teks Al-Quran, tafsir, buku-buku sejarah Islam, dan penelitian terkait. Penelitian ini juga menggali pandangan ulama tentang tema ini. Hasil penelitian mengungkap bahwa praktik pernikahan dalam Islam telah mengalami perubahan signifikan seiring berjalannya waktu. Dari masa awal Islam yang melibatkan poligami yang banyak, perlahan-lahan, masyarakat Muslim mulai mengadopsi praktik monogami sebagai norma. Ayat 3 dalam QS Annisa memberikan pedoman etis terkait pernikahan poligami, menekankan pentingnya keadilan dalam hubungan pernikahan. Ini mempengaruhi pemahaman dan praktik pernikahan dalam Islam modern. Penelitian ini menghasilkan pemahaman yang lebih dalam tentang sejarah pernikahan dalam Islam dan bagaimana pesan dalam QS Annisa Ayat 3 telah mempengaruhi perubahan praktik pernikahan. Dampak utama adalah bahwa pesan tentang keadilan dan perlindungan hak-hak perempuan dalam pernikahan tetap relevan dalam konteks pernikahan Islam modern. Kesimpulan Penelitian ini yaitu Sejarah pernikahan dalam Islam mencerminkan evolusi dari poligami menuju monogami, dengan penekanan pada keadilan dan perlindungan hak-hak perempuan dalam pernikahan. Pesan dalam QS Annisa Ayat 3 terus memandu praktik pernikahan dalam Islam saat ini, menegaskan pentingnya etika dan kesetaraan dalam hubungan pernikahan.Kata Kunci : Histori, Pernikahan, Poligami, Monogami, Perspektif QS Annisa Ayat 3.